Investigating the role of teacher agency on adopting plurilingual methodologies in language teaching - Mokhtari Mirabadi, Farya (Working papers in Applied Linguistics and Linguistics at York, 2024)
This research paper explores the critical role of teacher agency in the implementation and effectiveness of plurilingual strategies in educational contexts. It investigates how teachers’ beliefs, identities, and capabilities influence their adoption of plurilingual methods and assesses the impact of these factors on curriculum design. The discussion focuses on the dualistic nature of teacher agency, which can both enable and limit teachers as they deal with the complexities of plurilingual education. The paper reviews literature that illuminates the challenges and possibilities created by teacher agency, providing insights into how it shapes educational strategies and outcomes. It offers recommendations on how teacher education programs can leverage this agency to enhance plurilingual education effectively. This paper not only clarifies essential concepts but also critically examines the role of agency in advancing plurilingual educational practices, deepening the understanding of its application across educational settings.